VARIAÇÃO DA COMPOSIÇÃO DO VENENO DE FORMIGAS RECÉM-EXTRAÍDO E APÓS CONGELAMENTO EMPREGANDO CLAE-DAD - ORSO, Deise Maria; PIVA, Raul; SANTOS-JUNIOR, Luiz Carlos; BERNARDI, Rafaella Caroline; ANTONIALLI-JUNIOR, William Fernando; CARDOSO, Claudia Andrea Lima (ANAIS DO ENIC, 2017)
-